2017
DOI: 10.1007/s12298-017-0419-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability in Tunisian populations of faba bean (Vicia faba L. var. major) assessed by morphological and SSR markers

Abstract: The genetic diversity of 21 faba bean populations was examined using morphological and molecular markers. DNA was extracted from 189 individuals and 8 microsatellite markers were genotyped individually in these 21 populations. A total of 53 alleles were obtained in all populations, with an average of 6.62 alleles per locus. The expected and observed heterozygosity was 0.38 and 0.62 respectively. The average polymorphism index content of SSR markers was 0.61, ranging from 0.31 to 0.81. The unweighted pair group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
12
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 53 publications
9
12
0
4
Order By: Relevance
“…The polymorphic information content which is a measure of allelic diversity based on allele frequency (Smith et al, 2000) ranged from 0.00 to 0.97 with a mean of 0.52 (Table 3). The mean PIC value in the current study was comparable to those reported in other cultivated legumes including common bean , soybean (Chauhan et al, 2015), cowpea (Ali et al, 2015), groundnut (Otenga-Frimpong et al, 2015) and faba bean (Rebaa et al, 2017). Three of the genomic microsatellites (e.g.…”
Section: Discussionsupporting
confidence: 86%
“…The polymorphic information content which is a measure of allelic diversity based on allele frequency (Smith et al, 2000) ranged from 0.00 to 0.97 with a mean of 0.52 (Table 3). The mean PIC value in the current study was comparable to those reported in other cultivated legumes including common bean , soybean (Chauhan et al, 2015), cowpea (Ali et al, 2015), groundnut (Otenga-Frimpong et al, 2015) and faba bean (Rebaa et al, 2017). Three of the genomic microsatellites (e.g.…”
Section: Discussionsupporting
confidence: 86%
“…The results of critical analysis of seed color of faba bean germplasm accessions at the laboratory indicated least variation in seed coat color pattern but large variation seed size characters ( Table 2). These variations observed in seed size among the collected samples of indigenous Omani accessions are in conformity with those observed in previous studies that dealt with either local small or large germplasm collections [4,7,[17][18]. (Terzopolous et al, 2003;Kaur et al, 2014;Gasim et al, 2015;Rebaa et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…These variations observed in seed size among the collected samples of indigenous Omani accessions are in conformity with those observed in previous studies that dealt with either local small or large germplasm collections [4,7,[17][18]. (Terzopolous et al, 2003;Kaur et al, 2014;Gasim et al, 2015;Rebaa et al, 2017). In the present study, villages located closely with the collecting sites appeared to have interestingly either similar patterns of seed coat color indicating the presence of large amount of homogeneity in the collected faba bean seed samples/ accessions whereas heterogenous seed samples were found in seed samples from three different sites.…”
Section: Discussionsupporting
confidence: 91%
“…The evaluation of genetic variability among faba bean landraces using agro-morphological and molecular markers revealed that sequence-related amplified polymorphism (SRAP) and amplified fragment length polymorphism (AFLP) markers are used to determine the genetic variability among genotypes (Ammar et al 2015;Backouchi et al 2015;Abid et al 2015;Rebaa et al 2017;Alemu et al 2018). AFLP markers and combined SRAP are considered to be remarkably beneficial for the evaluation of genetic variability at the molecular level.…”
Section: Introductionmentioning
confidence: 99%